2012
DOI: 10.1007/s10895-012-1134-1
|View full text |Cite
|
Sign up to set email alerts
|

Europium Coordination Complexes as Potential Anticancer Drugs: Their Partitioning and Permeation Into Lipid Bilayers as Revealed by Pyrene Fluorescence Quenching

Abstract: The present study was undertaken to evaluate the membrane-associating properties of a series of novel antitumor agents, Eu(III) coordination complexes (EC), using the pyrene fluorescence quenching as an analytical instrument. Analysis of EC-induced decrease in pyrene fluorescence intensity in terms of partition and solubility-diffusion models allowed us to evaluate the partition and permeation coefficients of the examined compounds into the lipid vesicles prepared from zwitterionic lipid phosphatidylcholine (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…The premise of these measurements is that pyrene, acting as an environmental probe, will partition into the more hydrophobic drug-rich phase created during the process of LLPS. The use of pyrene to characterize surfactant micelle formation, , as well as probe lipid bilayers, , is widely established. Based on this body of literature, as well as previous studies from our group using pyrene, a change in the ratio of two characteristic pyrene emission peaks ( I 1 at 373 nm, I 3 at 383 nm) was used to indicate a change in the probe environment and consequently the LLPS concentration.…”
Section: Methodsmentioning
confidence: 99%
“…The premise of these measurements is that pyrene, acting as an environmental probe, will partition into the more hydrophobic drug-rich phase created during the process of LLPS. The use of pyrene to characterize surfactant micelle formation, , as well as probe lipid bilayers, , is widely established. Based on this body of literature, as well as previous studies from our group using pyrene, a change in the ratio of two characteristic pyrene emission peaks ( I 1 at 373 nm, I 3 at 383 nm) was used to indicate a change in the probe environment and consequently the LLPS concentration.…”
Section: Methodsmentioning
confidence: 99%
“…This helps the penetration through the lipid membranes, disturbing the functioning of the bacterial/fungal cell. Moreover, the anticancer activity of lanthanides was also evaluated and several Eu(III) complexes were synthesized and tested, showing some promising results as new anticancer agents [ 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, this mechanism seems to be unlikely as the europium chelates under study were highly hydrophobic compounds. [ 4–6 ] Conversely, Tajmir‐Riahi reported that the association of a number of drugs with albumin was accompanied by a decrease in α‐helix content in favour of β‐sheet and turn structures, which may be indicative of partial protein unfolding. [ 20 ] The route by which a polypeptide chain changes its conformation is thought to be similar to protein unfolding upon heating and is related to alterations in the contribution of the T Δ S term into Gibbs free energy.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous studies have focused on the interactions between a series of novel EC and the lipid bilayer, a major structural element of cellular membranes. [ 4–6 ] Analysis of the membrane‐associating and bilayer‐modifying properties of the europium chelates provided evidence for their accumulation in a lipid phase coupled with no significant effect on membrane integrity, thereby highlighting the possibility for development of EC liposomal formulations.…”
Section: Introductionmentioning
confidence: 99%